From Oil to Oil: A History of The Niger Delta Oil Economy from Palm Oil to Crude Oil, 1900 to 2019 - Bem, Japhet (Advances in Humanities and Contemporary Studies, 2022)
The Niger Delta is a ‘child of irony’, which produces one of the best crude oils in the world and solely sustains the Nigerian economy. Yet, the region wallows in extreme poverty, and lacks some of the most basic social amenities. This paper therefore, traces the history of the Niger Delta in relations to its contribution to the Nigerian economy through its oil welth. The paper adopts the historical-narrative approach. It also discusses the Slave Trade in the Niger Delta, the Era of Legitimate trade, the discovery and exploration of crude oil from 1956 to 1989. The paper concludes by examining the Niger Delta agitations, beginning with the Ogoni movement to the Niger Delta militancy, amnesty and post-Amnesty periods. The paper finds out that socio-political factors are responsible for the backwardness of the region despite its oil wealth.